Enhancement of Lipolysis in 3T3-L1 Adipocytes by Nitroarene Capsaicinoid Analogs - Thanet Laolob (2022)
Transient receptor potential vanilloid 1 (TRPV1) activation by capsaicin binding increased intracellular calcium influx and stimulated adipocyte-to-adipocyte communication, leading to lipolysis. Generally, enhancement of π-stacking capabilities improves certain binding interactions. Notably, nitroarenes exhibit strong binding interactions with aromatic amino acid side chains in proteins. New capsaicinoid analogs were designed by substitution of the OCH3 group with a nitrogen dioxide (NO2) group on the vanillyl ring to investigate how π-stacking interactions in capsaicinoid analogs contribute to lipolysis. Capsaicinoid analogs, nitro capsaicin (5), and nitro dihydrocapsaicin (6) were prepared in moderate yields via coupling of a nitroaromatic amine salt and fatty acids. Oil Red O staining and triglyceride assays with 10 µM loading of capsaicin (CAP), dihydrocapsaicin (DHC), 5, and 6 were performed to investigate their effect on lipolysis in 3T3-L1 adipocytes. Both assay results indicated that 5 and 6 decreased lipid accumulation by 13.6% and 14.7%, respectively, and significantly reduced triglyceride content by 26.9% and 28.4%, respectively, in comparison with the control experiment. Furthermore, the decrease in triglyceride content observed in response to nitroarene capsaicinoid analogs was approximately 2-folds higher than that of CAP and DHC. These results arose from the NO2 group augmented π-π stacking with Tyr511 and the attractive charge interaction with Glu570 affecting binding interactions with TRPV1 receptors.